Semantic transition in media-specialized terms: Study and analysis - Alkhateeb, Samah Yonis (Journal of Arabic Language Sciences and Literature, 2022)
Although there are too many lists that collect words but these lists are limited. While there are too many list that, explain the meanings of these terms unlimitedly. They develop, change and transfer in the linguistic system and in the general lingual usage regularly. Based on that create a new usage of words which become as a rich recourse of development and semantic transition for using the new terms. This study based on following the semantic transition for a group of media terms in Arabic dictionaries, and show their usage in Qur’an, then making the terms clear in media dictionary, according to an approach, its aim is the researching in the semantic transition which occurred on the terms, trying to follow the origin of its usage, the stages of meanings’ transition, analyzing the way of settling down to a certain term, looking for the beyond of semantic transition method, it also explains the purpose of meaning’s change as a type of semantic development and defining its types and the reasons of its existence.